2015
DOI: 10.1091/mbc.e15-01-0043
|View full text |Cite
|
Sign up to set email alerts
|

The rod domain is not essential for the function of plectin in maintaining tissue integrity

Abstract: Plectin is a cytoskeletal linker protein that consists of a central rod domain connecting two globular domains. Rodless plectin is able to functionally compensate for the loss of full-length plectin in mice and, like full-length plectin, is able to form dimers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 61 publications
0
26
0
Order By: Relevance
“…5B). Previous studies have demonstrated low nesprin-3 expression within the epidermis, and mice lacking nesprin-3 have a normal skin phenotype (Ketema et al, 2013). These findings suggest that in keratinocytes, plectin and nesprin-3 do not directly link keratins to the nuclear membrane.…”
Section: Resultsmentioning
confidence: 80%
“…5B). Previous studies have demonstrated low nesprin-3 expression within the epidermis, and mice lacking nesprin-3 have a normal skin phenotype (Ketema et al, 2013). These findings suggest that in keratinocytes, plectin and nesprin-3 do not directly link keratins to the nuclear membrane.…”
Section: Resultsmentioning
confidence: 80%
“…The gene sequences encoding these eight isoforms 1, 1a, 1b, 1c, 1d, 1e, 1f, and 1g differ in their first exons and the corresponding upstream regulatory sequences (Fuchs et al, 1999;Rezniczek et al, 2003). Additionally, alternative splicing of exon 31 results in a rodless plectin variant, which has been identified in human keratinocytes and skeletal muscle plectin (Ketema et al, 2015;Winter and Wiche, 2013).…”
mentioning
confidence: 99%
“…A central rod domain (ϳ1250 amino acids) is responsible for homodimerization via coiled-coil interactions. Most of the rod domain is absent in a natural rod-less splice variant that retains the function of the full-length protein (11). Finally, the C-terminal region contains six plakin repeat domains and mediates binding to IFs (12).…”
mentioning
confidence: 99%